Hot electron bolometer sensors for millimetre-wave and terahertz wave detection - Northeast, David Bernard (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Electrical and Electronic Engineering))--Univerity of Stellenbosch, 2011.